ANALISIS PENGGUNAAN ARTICULATE STORYLINE 3.0 DENGAN PENDEKATAN DEEP LEARNING DALAM MENCAPAI KOMPETENSI LITERASI DIGITAL SEBAGAI UPAYA MEWUJUDKAN PENDIDIKAN BERKUALITAS (SDGS4) - Nur Ashifa, Isqi; Fatkhomi, Fahmi; Nur Hayati, Muriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the impact of using Articulate Storyline 3.0 media with a deep learning approach on students' digital literacy competence in the context of achieving quality education (SDGs 4). The study was motivated by the limited use of interactive digital media and low student digital literacy in science learning. A quasi-experimental method with a posttest-only control group design was employed. The sample consisted of two groups: an experimental group (using Articulate Storyline 3.0) and a control group (using PowerPoint). Instruments included questionnaires covering four digital literacy competence areas: Information and Data Literacy, Communication and Collaboration, Problem Solving, and Digital Content Creation. Results showed that in the experimental class, the Information and Data Literacy competence area achieved the highest score (80.5%), while Problem Solving was the lowest (75%). In the control class, the highest score was in Communication and Collaboration (73.30%) and the lowest in Problem Solving (65.49%). These findings indicate that Articulate Storyline 3.0 with a deep learning approach is more effective in supporting the mastery of data and information literacy as well as comprehensive digital skills, whereas PowerPoint excels in collaboration but is less effective in fostering optimal digital literacy mastery.